Uric Acid as a Predictor of the Severity of Preeclampsia: A Cross-Sectional Study in Sidi Bel Abbes, Algeria - Bouanani, Fatima Zohra; El kadi, Fatima Zohra; Meghit , Boumediene Khaled; Benmalek , Djihène Narimène; Bouragba , Imane (AL-Kindy College Medical Journal, 2025)
Background: Preeclampsia is a pregnancy complication characterized by elevated blood pressure and organ failure, endangering the health of both the fetus and the mother. The research aimed to examine the predictive value of uric acid levels on outcomes in preeclamptic pregnant women.Subjects and Methods: The study consisted of 151 preeclamptic pregnant women, categorized into two groups: 99 with severe preeclampsia (SPG) and 52 with moderate preeclampsia (MPG).  The researchers compared uric acid levels between groups and looked at LDH, ASAT, and ALAT biomarkers.  The study employed Receiver Operating Characteristic (ROC) curve analysis to evaluate the predictive capacity of uric acid levels regarding outcomes.Results: The study revealed that women with severe preeclampsia exhibited markedly elevated uric acid levels (p = 0.003).  The cohort with severe preeclampsia encountered more pronounced feto-maternal complications at a statistically significant level (p ≤ 0.001).  The ROC curve analysis indicated that uric acid levels exhibited a moderate capacity to predict the severity and complications of preeclampsia, with diagnostic accuracy rates of 0.691 (p≤0.001) and 0.635 (p=0.007), respectively.  The predictive value of uric acid was demonstrated to be inferior to that of the other biomarkers in the study.Conclusions: While elevated uric acid levels are associated with preeclampsia severity, they may not be as strong a predictor of adverse outcomes as other biomarkers such as ASAT, ALAT, and LDH.